The timecourse of apoptotic cell death during postnatal remodeling of the mouse cochlea and its premature onset by triiodothyronine (T3). (15th May 2015) - Peeters, R.P.; Ng, L.; Ma, M.; Forrest, D.
Highlights: The timecourse of apoptosis during postnatal remodeling of the cochlea is reported. T3 stimulates the program of apoptosis in the greater epithelial ridge. Evidence supports a TRβ receptor-mediated mechanism of apoptosis. Abstract: Apoptosis underlies various forms of tissue remodeling during development. Prior to the onset of hearing, thyroid hormone (T3) promotes cochlear remodeling, which involves regression of the greater epithelial ridge (GER), a transient structure of columnar cells adjacent to the mechanosensory hair cells. We investigated the timecourse of apoptosis in the GER and the influence of ectopic T3 on apoptosis. In saline-treated mice, activated caspase 3-positive cells were detected in the GER between postnatal days 7 and 13 and appeared progressively along the cochlear duct from base to apex over developmental time. T3 given on P0 and P1 advanced the overall program of apoptosis and remodeling by 4 days. Thyroid hormone receptor β was required for these actions, suggesting a receptor-mediated process of initiation of apoptosis. Finally, T3 given only at P0 or P1 resulted in deafness in adult mice, thus revealing a transient period of susceptibility to long-term damage in the neonatal auditory system.